Glycyrrhizin Attenuates Salmonella enterica Serovar Typhimurium Infection: New Insights Into Its Protective Mechanism - Xu, Xiaogang; Gong, Li; Wang, Baikui; Wu, Yanping; Wang, Yang; Mei, Xiaoqiang; Xu, Han; Tang, Li; Liu, Rongrong; Zeng, Zhonghua; Mao, Yulong; Li, Weifen (Frontiers in Immunology, 2018)
Glycyrrhizin (GL), a triterpenoid glycoside, serves important functions in various biological activities, including antiviral and antitumor immune responses. However, the anti-inflammatory effects of GL on Salmonella enterica serovar Typhimurium (ST)-induced injury in mice and the mechanisms underlying the protection of GL are poorly understood. Here, we investigated the effects of GL on host immune responses against ST infection in mice. A phenotypic analysis using hematoxylin and eosin (H&E) staining and transmission electron microscopy showed that GL relieved ST-induced weight loss and intestinal mucosal injury. A colonization assay showed that GL significantly reduced ST colonization in the ileum and colon and translocation to the liver and spleen. An antibacterial activity assay and real-time PCR revealed that GL had no direct inhibitory impact on ST growth or virulence gene expression. ELISA showed that GL pretreatment significantly decreased proinflammatory cytokine (IFN-γ, TNF-α, IL-6) secretion and increased anti-inflammatory cytokine (IL-10) secretion in the ileum, colon, and serum of ST-infected mice. Moreover, flora analysis showed that GL reduced Akkermansia, Sutterella, Prevotella, and Coprococcus but enriched Parabacteroides and Anaerotruncus in the cecum of ST-infected mice. These results suggest that GL promotes the secretion of immune factors and modulates intestinal flora to prevent further ST infection. We also analyzed the effect of GL on immunocytes and found that GL promoted the phenotypic and functional maturation of murine bone marrow-derived dendritic cells (BMDCs). Flow cytometry and western blotting demonstrated that NF-κB, ERK, and p38 MAPK were required for GL-induced BMDC maturation. The above ﬁndings indicate that GL attenuates ST infection by modulating immune function and intestinal flora. This study enriches our current knowledge of GL-mediated immunological function and provides a new perspective on the prevention of Salmonella infection in animals and humans.